Initial statin dose after myocardial infarction and long-term cardiovascular outcomes - Kytö Ville; Rautava Päivi; Tornio Aleksi (Oxford University Press, 2025)
Aims
Effective statin therapy is a cornerstone of secondary prevention after myocardial infarction (MI). Real-life statin dosing is nevertheless suboptimal and largely determined early after MI. We studied long-term outcome impact of initial statin dose after MI.
Methods and results
Consecutive MI patients treated in Finland who used statins early after index event were retrospectively studied (N = 72 401; 67% men; mean age 68 years) using national registries. High-dose statin therapy was used by 26.3%, moderate dose by 69.2%, and low dose by 4.5%. Differences in baseline features, comorbidities, revascularisation, and usage of other evidence-based medications were adjusted for with multivariable regression. The primary outcome was major adverse cardiovascular or cerebrovascular event (MACCE) within 10 years. Median follow-up was 4.9 years. MACCE was less frequent in high-dose group compared with moderate dose [adjusted hazard ratio (HR) 0.92; P < 0.0001; number needed to treat (NNT) 34.1] and to low dose [adj.HR 0.81; P < 0.001; NNT 13.4] as well as in moderate-dose group compared with low dose (adj.HR 0.88; P < 0.0001; NNT 23.4). Death (adj.HR 0.87; P < 0.0001; NNT 23.6), recurrent MI (adj.sHR 0.91; P = 0.0001), and stroke (adj.sHR 0.86; P < 0.0001) were less frequent with a high- vs. moderate-dose statin. Higher initial statin dose after MI was associated with better long-term outcomes in subgroups by age, sex, atrial fibrillation, dementia, diabetes, heart failure, revascularisation, prior statin usage, or usage of other evidence-based medications.
Conclusion
Higher initial statin dose after MI is dose-dependently associated with better long-term cardiovascular outcomes. These results underline the importance of using a high statin dose early after MI.